Translanguaging in English teaching in higher education - Hoan, Pham Thi Khai; Anh, Vu Thi Phuong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Recently, whether to use translanguaging in teaching English has received great attention from language researchers and language teachers all over the world. This critical review aims to systematically synthesize literature on the use of translanguaging in teaching English in higher education. Research results show that translanguaging has added a new dimension to the long-standing debate on the use of mother tongue (L1) in foreign language teaching/learning because it basically emphasizes viewing language as a unitary system in contrast to the traditional perception that each language belongs to a separate system. The revolution in the perceptions of the importance of using L1 in foreign language teaching/ learning is justified because translanguaging promotes a more effective teaching and learning process. However, students' native language must be used strategically in the classroom with the aim of facilitating and supporting the teaching process and enabling learners to develop comprehension, communication skills and acquisition of the target language.